Characteristics of karst geothermal system in intermountain fault basin: a case study of Taiyuan basin in north China - Tinghao, Wang; Xinwei, Wang; Xuan, Zhang; Lu, Luo; Huiying, Liu (Frontiers in Earth Science, 2026)
IntroductionThe Taiyuan Basin of North China, as a typical intermountain fault basin, is located in the middle part of the Fen-Wei graben system-an extensional faulting belt. It is one of the areas where high-quality karst thermal storage is developed to match urban heating demand. The formation of its karst geothermal system and the study of its thermal storage characteristics are of great significance for analyzing the distribution pattern of this type of geothermal resource and its overall development.MethodsBased on the synthesis of previous research results and the latest geothermal well data, this article analyzes the heat source, karst geothermal reservoir distribution, and hydrothermal dynamic characteristics of the karst geothermal system in the Taiyuan Basin, and evaluates the geothermal resources in 8 units.ResultsThe results show as flow: (1) The karst geothermal reservoir strata in the Taiyuan Basin are mainly composed of the Lower Paleozoic Ordovician, widely distributed in the North China Plate. The evolution of karst geothermal systems has gone through five stages from the Early Paleozoic to the Quaternary. (2) The heat source comes from the high-altitude heat flow (>71 mW/m2) in the asymmetric fault basin of the Cenozoic era, and the heat transfer mode can be divided into the basin edge strong convolution type and the basin internal heat conduction type. (3) The cumulative thickness of the geothermal effective reservoir section is 160–180 m, including the main water bearing sections of 3-4 layers, which are prone to overflow during migration. (4) Controlled by the structure and topography of mountain fault basins, the geothermal water supply and transport mode of karst geothermal systems has the characteristics of bidirectional, near source, and rapid.DiscussionAccording to the evaluation method of karst geothermal reservoir volume, the total geothermal resources of the karst geothermal system in Taiyuan Basin are estimated to be 83.03 × 108 GJ, equivalent to 2.83 × 108t standard coal, and the annual mining output can meet the heating area of 15 million square meters.